2004
DOI: 10.1148/radiol.2323030359
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypoplasia: Prediction with Use of Ratio of MR Imaging–measured Fetal Lung Volume to US-estimated Fetal Body Weight

Abstract: The FLV/FBW reflects the adequacy of intrauterine lung growth and can help predict PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 16 publications
2
20
0
6
Order By: Relevance
“…This is in concordance with numerous previous publications on this topic, which investigated the degree of pulmonary hypoplasia on fetal MR imaging and correlated that with the severity of neonatal outcomes [7,9,14,20,22,23,46,47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in concordance with numerous previous publications on this topic, which investigated the degree of pulmonary hypoplasia on fetal MR imaging and correlated that with the severity of neonatal outcomes [7,9,14,20,22,23,46,47].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to 2D and 3D ultrasound studies, the potential of MR imaging in the assessment of lung hypoplasia and the prediction of mortality has been validated, and has been shown to be reliable for the prenatal investigation of lung hypoplasia compared with US [5][6][7][8]. Most MR imaging studies have dealt with the volumetric assessment of the lung, where lung volumes were found to be significantly reduced in fetuses with CDH [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, at 33 weeks, a great increase in size of the hyperechogenic lesion was observed, caused by a large cyst ( Figure 1) associated with polyhydramnios (amniotic fl uid index of 46) and preterm labor. The ratios of observed/expected fetal lung volume, 5 ultrasonographic lung/body weight 6 and cyst/lung volume were 0.22, 0.005 and 6.99 respectively (Figures 2 and 3). The patient was hospitalized: tocolysis was performed using intravenous terbutaline for 12 hours, 2.5 liters of amniotic fl uid were drained and a cyst-amniotic shunt (Harrison Fetal Bladder Stent Set, Cook Medical Inc., United States) was placed.…”
Section: Case Reportmentioning
confidence: 93%
“…Die Autoren um Tanigaki et al konnten zeigen, dass eine Vorhersage einer Lungenhypoplasie durch das Verhältnis von MR-tomografisch gemessenem Lungenvolumen zum mittels Sonografie bestimmten fetalen Körpergewicht besser möglich war als mit den nur per Ultraschall ermittelten Zirkumferenzquotienten von Thorax zu Abdomen oder interthorakalen Quotienten. Bei Feten mit pulmonaler Hypoplasie war in dieser Arbeit der Quotient mit 0,012 ml/g ± 0,008 signifikant niedriger als bei der Kontrollgruppe mit 0,028 ml/g ± 0,007 (p < 0,001) [40]. Das mit der MRT ermittelte Lungenvolumen stellt einen prädiktiven Faktor für die Abschätzung der postnatalen Mortalität des Feten dar [41].…”
Section: Huisman Et Al Und Fogliarini Mit Girard Et Al Haben In Ihrenunclassified